Delia Lawrie interviewed by Baiba Berzins - Lawrie, Delia, 1966-; Berzins, Baiba Beata, 1944- (2001)
Lawrie speaks of how her father and mother met and married, her education, the impact of Cyclone Tracy when she was only age 8 and her eventual evacuation to Melbourne, what made her to decide to become a journalist, how her upbringing taught to her to conduct herself well publicly, how dinner table discussion stimulated her interest in politics and particular people who influenced her political views; her cadetship in journalism with NT News and how she had to overcome sexist barriers to being trained as a reporter, why she resigned after one year as a journalist, moved to Melbourne and continued her cadetship with Leader Associated Newspapers, how she became active in the Victorian Branch of the Australian Journalists' Association, after 8 years in Melbourne travelled overseas and worked in Hong Kong for three and half years on two newspapers, her work with Vietnamese refugees, after more travelling returned to Hong Kong where she married, returned to Darwin in 1995 when pregnant with her first child.
Lawrie speaks of working for Clare Martin during her election campaign, moved to Adelaide until 1999 when she moved back to Darwin for family reasons becoming Executive Director, N.T. Carers' Association, then Editor of the Darwin Sun newspaper, later encouraged to stand for pre-selection for the seat of Karama which she eventually won.
Recorded on Oct. 8, 2001 at Karama, Darwin, N.T.
Digital master available
Delia Lawrie - journalist and politician
Timed summary available (4 p.)
Keywords: Lawrie, Delia, -- 1966- -- Interviews; Newspapers -- Hong Kong; Politicians -- Northern Territory -- Interviews; Journalists -- Australia -- Interviews